Solved Problems in Nonlinear Oscillations A sourcebook for scientists and engineers - He, Zeng.; Jiang, Wen.; Wang, Lin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This is an open access book. This textbook contains about 200 fully solved problems in analytical and numerical methods for nonlinear osccillations. These comprise all the end-of-chapter problems in Ali H. Nayfeh and Dean T. Mook$1 (Bs famous textbook Nonliear Oscillations. Mathematical software are adopted to make those solutions more accessible from a graphical point of view. This book can be adopted as a supplement to course work study for graduates or senior undergraduates. Since many exercise problems are adapted from scientific research papers, this book also has a good reference value for scientists and engineers who work in nonlinear vibration.s
Problem Lists -- Conservative Single-Degree-of-Freedom Systems -- Nonconservative Single-Degree-of-Freedom Systems -- Forced Oscillations of Systems Having a Single Degree of Freedom -- Parametrically Excited Systems -- Systems Having Finite Degrees of Freedom -- Continuous Systems -- Traveling Waves.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Multibody systems; Vibration; Mechanics, Applied; System theory; Control theory; Dynamical systems; Continuum mechanics; Multibody Systems and Mechanical Vibrations; Systems Theory, Control; Dynamical Systems; Continuum Mechanics